2017
DOI: 10.1007/s11218-017-9394-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among Bi-ethnic students and differences in educational outcomes and social functioning

Abstract: The number of bi-ethnic children is increasing. The focus of this study is on bi-ethnic students in the Netherlands with one parent with an ethnic majority background and one parent with an ethnic minority background. Most studies that have investigated educational outcomes and social functioning in school for biethnic students have not focused on the diversity within this group. In this study, we described the demographic, social and cultural diversity among bi-ethnic students and examined whether, in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Limited language proficiency in the national language partially explains lower academic performances of non-native students as compared to their native peers OECD 2010). In the current article, the term native refers to students whose parents are both of Dutch origin (i.e., non-migrant; those who speak Dutch as a native language), whereas nonnative designates those students of whom at least one of his or her parents were born in other, often non-Western European countries (i.e., first or second generation migrants; those who speak Dutch as a minority language; Karssen et al 2017). Oortwijn et al (2005) found that non-native students' lack of proficiency in the national language is especially detrimental for their performance on contextualized mathematics tasks when compared to native students.…”
Section: Introductionmentioning
confidence: 99%
“…Limited language proficiency in the national language partially explains lower academic performances of non-native students as compared to their native peers OECD 2010). In the current article, the term native refers to students whose parents are both of Dutch origin (i.e., non-migrant; those who speak Dutch as a native language), whereas nonnative designates those students of whom at least one of his or her parents were born in other, often non-Western European countries (i.e., first or second generation migrants; those who speak Dutch as a minority language; Karssen et al 2017). Oortwijn et al (2005) found that non-native students' lack of proficiency in the national language is especially detrimental for their performance on contextualized mathematics tasks when compared to native students.…”
Section: Introductionmentioning
confidence: 99%